Simplified Model Characterization and Control of an Unmanned Surface Vehicle - Aldo Lovo-Ayala; Roosvel Soto-Diaz; Carlos Andres Gutierrez-Martinez; Jose Fernando Jimenez-Vargas; Javier Jiménez-Cabas; Jose Escorcía-Gutierrez (Journal of Marine Science and Engineering)
This study presents the modeling and control of the unmanned surface vehicle (USV) SABALO. Two models were built, one based on a transfer function matrix and another based on state variables, and from these models, two control strategies were developed. The first strategy is based on independent Proportional-Integral/Proportional-Derivative (PI/PD) controllers complemented by a decoupling system, and the second strategy is based on state variable feedback. The two control strategies were evaluated and contrasted. Results demonstrated that the decoupler effectively eliminated variable interaction, enhancing stability in straight trajectories and directional changes. Meanwhile, state feedback control demonstrated markedly faster response times and superior precision, accompanied by higher energy consumption. The study concludes that both strategies are effective, but their suitability depends on the mission. The decoupler could be ideal for energy-efficient, long-duration operations, while state feedback could be appropriate for dynamic environments requiring rapid maneuvers.